Creative ecologies: developing and managing new concepts of creative economy - Stankevičienė, Jelena; Levickaitė, Rasa; Braškutė, Monika; Noreikaitė, Elinga (Business, Management and Economics Engineering, 2011)
The idea of creativity is becoming more and more relevant and is observed in various fields, such as contemporary economics, technology and science. This article is based on the creative ecology theory which has emerged from the creative economy theory developed by economist John Howkins. According to him, it is fundamental to understand the current crisis in the natural environment and economy, and the balance of creativity and control required in our response. The article is based on three research questions: 1) what are the fundamental principles of creativity and the process of sustainable creation; 2) how can one develop high quality ideas and turn them into reality; 3) is it possible for the reckless consuming society to share sustainable creative products and how could this be achieved. Creative economy is a rapidly growing sector of world market. Howkins (2010) uses the creative ecologies theory to analyse human creativity and abilities to create. Creative ecology is presented as “a niche where diverse individuals express themselves in a systemic and adaptive way, using ideas to produce new ideas; and where others support this endeavour even if they don’t understand it”. Four aspects (diversity, change, learning, adaptation) of ecological thinking are presented as directly related to creativity and innovations, thus extremely important to any contemporary organisation seeking leadership in the creative economy. Looking into the new concept of creativity, authors of the article came to the conclusion that a sustainable relationship between creativity and science is a necessary tool for change, development and management of new concepts of creative economy. The article is based on the project Creative Ecologies: Creating, Developing and Sharing Sustainable Ideas presented by the authors in the Euroweek 2011 conference Water4World. The project received two awards – the 1st prize in the project section and The Best Project of the Euroweek 2011.